Strategi Inovasi Produk dalam Menghadapi Persaingan Usaha Home Industri - Junaedi, Deddy; Aini, Lutfiyah Qilfa Khoiril; Nurhalisa, Siti; Rustina, Siti Ayu; Handayani, Ririn Yanti; Jannah, Lailatul (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This research explores the product innovation strategies implemented by the home-based business